2017
DOI: 10.7863/ultra.16.07032
|View full text |Cite
|
Sign up to set email alerts
|

The Serial Duplex Index Improves Differential Diagnosis of Acute Renal Transplant Dysfunction

Abstract: The developed SDI was able to detect acute renal transplant rejection with greater sensitivity and specificity than the RI and PI ratios. Since the SDI distinguishes between acute tubular necrosis, acute cellular rejection, and acute vascular rejection, it might be a supportive tool to indicate renal biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…Similar to our result, Köhnke et al showed low sensitivity and low specificity of RI in the identification of acute renal allograft rejection [7]. Meier et al introduce the serial duplex index (SDI = [(RI t0 /RI t-1 ) × (PI t0 /Pi t-1 )]/(CPP t0 /CPP t-1 ), were CPP = cortex-pelvis proportion, PI = pulsatility index, t0 = values from the day of biopsy, t-1 = values from three to seven days before biopsy) and investigated how its value varies on normal kidney graft function, acute tubular necrosis, acute cellular rejection and acute vascular rejection [39]. However, age [40], pulse pressure, heart rate and cardiac rhythm [41] affect the RIs values and thus could explain the controversially RI results on kidney allograft evaluation [37,40,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our result, Köhnke et al showed low sensitivity and low specificity of RI in the identification of acute renal allograft rejection [7]. Meier et al introduce the serial duplex index (SDI = [(RI t0 /RI t-1 ) × (PI t0 /Pi t-1 )]/(CPP t0 /CPP t-1 ), were CPP = cortex-pelvis proportion, PI = pulsatility index, t0 = values from the day of biopsy, t-1 = values from three to seven days before biopsy) and investigated how its value varies on normal kidney graft function, acute tubular necrosis, acute cellular rejection and acute vascular rejection [39]. However, age [40], pulse pressure, heart rate and cardiac rhythm [41] affect the RIs values and thus could explain the controversially RI results on kidney allograft evaluation [37,40,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, Meier et al investigated if a newly developed serial duplex index (SDI) can be used to differentiate between AR and acute vascular rejection more effectively in comparison with the established Doppler parameters RI and pulsatility index (PI) in the first days after the transplantation [31]. The PI represents a Doppler derived index that depends on downstream renal artery resistance and stiffness [32].…”
Section: Ultrasoundmentioning
confidence: 99%
“…Patients in the CRS and CKD groups had undergone kidney ultrasound examination performed in the nephrology outpatient center by three experienced investigators and echocardiographic examination at the cardiology department of the Hospital of Reinbek, St. Adolf Stift between 2014 and 2017. The NRF group had undergone both ultrasound and echocardiographic examination at the Medical Department of the University of Lubeck between 2007 and 2014, as described previously 9 10 . The renal ultrasound examinations of these patients had been performed by the same three experienced investigators (MM; MN, WJ) who performed the investigations of the CKD and CRS group in the same standardized protocol (described below) a few years later.…”
Section: Methodsmentioning
confidence: 99%
“…Data regarding both routine grayscale and duplex ultrasound scans were obtained for all enrolled patients. The standard ultrasound examination protocol applied for the patients included in the current study has been outlined previously 9 10 and is as follows: Ultrasound examination was performed in the supine position during the morning hours by one of the three authors using the same transducers (multifrequency probes, curved array, C4-1, C9-3 or C6-2, Zonare Medical Systems, Mountain View, Ca, USA) and devices (Z.one and ZS3, Zonare Medical Systems, Mountain View, CA, USA). The following parameters were measured and recorded during each ultrasound scan: the cortex-pelvis proportion (CPP), resistive index (RI), pulsatility index (PI), and venous velocity (VV).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation